PRELIMINARY INVESTIGATIONS FOR EXPLORING SCOPE OF POLLEN CRYOPRESERVATION FOR CONSERVATION OF POTATO GENETIC RESOURCES - RP Kaur (Potato Journal, 2019)
ABSTRACT: Pollen grains are a rich source of diverse alleles in any genepool and represent large genetic diversity in small sample size. Inherent hardiness and stability under harsh conditions make them an effective propagule for germplasm conservation using cryogenic storage. Cryopreservation was used to conserve pollen of six potato varieties namely Kufri Girdhari, Kufri Himalini, Kufri Himsona, Kufri Jyoti, Kufri Kanchan and Kufri Shailja at ICAR-Central Potato Research Institute, Shimla. Pollen collected were packed in gelusil capsules, kept in cryovials and immersed in liquid nitrogen. A single lot was tested after 24 hrs of cryopreservation using pollen germination technique and double staining with Alexanders stain, having malachite green for pollen cell wall staining (indigo-blue colour) and acid fuschine for pollen protoplasm (purple). Under similar conditions, the germination response of pollen of fresh and cryopreserved varieties was statistically at par, with heat-killed pollen as a negative control showing nil germination. The germination response among varieties varied from 4.6% (Kufri Jyoti) to 24.6% (Kufri Himalini). Low germination response was mainly attributable to pollen grains showing no protoplasm and having only indigo-blue staining walls, which may reportedly be due to abnormal meiotic segregation producing non-viable pollen in potato. The pollen tube lengths varied from 10 Î¼m to 500 Î¼m after 3 hours of incubation in medium, indicative of differences in pollen vigour. Â